## Which equation can be used to represent “six added to twice the sum of a number and four is equal to one-half of the difference of three and

Question

Which equation can be used to represent “six added to twice the sum of a number and four is equal to one-half of the difference of three and the number”?

6 + 2(x + 4) = (3 – x)

6 + 2(x + 4) = (x – 3)

(6 + 2)(x + 4) = (3 – x)

(6 + 2)(x + 4) = (x – 3)

in progress
0

Math
2 days
2021-10-10T23:30:03+00:00
2021-10-10T23:30:03+00:00 2 Answers
0
## Answers ( )

I would say its option (a)

But I’m confused why you put the one-half there, since I don’t see any halves.

Steps

Six added

6 +

to twice

6 + 2()

the sum of a number and four

6 + 2(x + 4)

is equal to

6 + 2(x + 4) =

The difference of three and the number.

6 + 2(x + 4) = (3 – x)

Answer:a. 6 + 2(x + 4) = (3 – x)

Step-by-step explanation: just took the test